2016
DOI: 10.1016/j.artint.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Generating SAT instances with community structure

Abstract: Nowadays, modern SAT solvers are able to efficiently solve many industrial, or realworld, SAT instances. However, the process of development and testing of new SAT solving techniques is conditioned to the finite and reduced number of known industrial benchmarks. Therefore, new models of random SAT instances generation that capture realistically the features of real-world problems can be beneficial to the SAT community. In many works, the structure of industrial instances has been analyzed representing them as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…Sonobe et al [ 9 ] improved the performance of a parallel SAT solver by using community structured partitioning. Giráldez-Cru and Levy [ 10 , 11 ] used the formula community to generate some highly modular pseudo-random industrial instances.…”
Section: Introductionmentioning
confidence: 99%
“…Sonobe et al [ 9 ] improved the performance of a parallel SAT solver by using community structured partitioning. Giráldez-Cru and Levy [ 10 , 11 ] used the formula community to generate some highly modular pseudo-random industrial instances.…”
Section: Introductionmentioning
confidence: 99%
“…The main aim of these studies is to better understand the success of CDCL techniques and help to improve them. They can also help develop new benchmarks generation models with more realistic properties [34][35][36][37][38][39][40]. This problem has been identified as an important challenge in the SAT community [41][42][43].…”
Section: Related Workmentioning
confidence: 99%
“…Markström in [ 26 ] proposed a constructor method of SAT instance based on Eulerian graphs, and discussed how a solver can try to avoid at least some of the pitfalls presented by these instances. Giraldez-Cru and Levy in [ 27 ] proposed a new model of generation of random SAT instances with community structure, and showed that modern solvers do actually exploit this community structure. In [ 28 ], they presented a random SAT instances generator based on the notion of locality, and showed that CDCL SAT solvers take advantage of both popularity and similarity.…”
Section: Related Workmentioning
confidence: 99%